Uma escuta ética do cuidado na morte e no morrer: o cotidiano de profissionais em um hospital pediátrico - Lima, Maria Juliana Vieira (2018)
Due to a socio-historical process, death has become a taboo for current society. There is a closing of the theme, away from the daily discussions and isolating their experience. Because of this, end-of-life or non-curable patients have little humanized care, emphasizing the supremacy of technique in care relations and a forgetting of the place of the other. In this context, the general objective of the research is to know the ethical principles of a health care of health professionals along with the children and adolescents in the process of death and dying, and to analyze the light from the perspective of the radical alterity in Emmanuel Lévinas; The specific objectives are to know, through the perspective of health professionals, the relationship their between patients in the process of death and dying; to discuss the care forms for patients and to identify the possibilities of action in this context. This is a qualitative research, based on the deconstruction proposal, in Jacques Derrida, and uses the everyday life research and the half-structured interview with health team of a pediatric public hospital in the State of Ceará to obtain data from the research. According to the results found, the opposites "Vivification of the Death and Mortification of Life" are put to dialogue. This relation refers to actions of the professionals that produced life in terminal situations through the realization of dreams, organization of birthday parties, respect for the patients' wishes, possibility of closings and farewells before death, as well as a focus on quality of life and respect for autonomy those. However, other actions produced mortification processes of life, when the patient's were not respected, a team decided in an arbitrary and non-dialogued way and, mainly, an exclusively technical care and without affective attachment. It is thus believed that the relationship with the other that occurs through vulnerability, exposure, sensitivity and passivity shows us possibilities of paths in the field of care that allowed the self get out from its place of sovereignty to give place to the other. Thus, we point out horizons of action that are not indifferent to suffering, that take responsibility for the processes of the subjects and care not to let the other alone in their suffering and their death, responding to the other: I AM HERE. As a result of the research, desert, we aim to create spaces to think about the relationship between ethics and care and to foster the development of ethical care relationships, benefiting patients and professionals.